2012
DOI: 10.1002/bies.201200076
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics meets mathematics: Towards a quantitative understanding of chromatin biology

Abstract: How fast? How strong? How many? So what? Why do numbers matter in biology? Chromatin binding proteins are forever in motion, exchanging rapidly between bound and free pools. How do regulatory systems whose components are in constant flux ensure stability and flexibility? This review explores the application of quantitative and mathematical approaches to mechanisms of epigenetic regulation. We discuss methods for measuring kinetic parameters and protein quantities in living cells, and explore the insights that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 97 publications
(161 reference statements)
3
24
0
Order By: Relevance
“…24 Its loss leads to a release of heterochromatin from the periphery in the nuclei of C. elegans embryos, perfectly fulfilling the initial experimental hypothesis. Furthermore, analysis of CEC-4 localization revealed that it is concentrated at the nuclear rim.…”
Section: Pathways Of Heterochromatin Sequestration At the Nuclear Persupporting
confidence: 71%
“…24 Its loss leads to a release of heterochromatin from the periphery in the nuclei of C. elegans embryos, perfectly fulfilling the initial experimental hypothesis. Furthermore, analysis of CEC-4 localization revealed that it is concentrated at the nuclear rim.…”
Section: Pathways Of Heterochromatin Sequestration At the Nuclear Persupporting
confidence: 71%
“…The extracted diffusion coefficients given by FCS and FRAP were in reasonably good agreement with each other, with the exception of EGFP:ASH1, for which a slower diffusion coefficient was extracted from FRAP than from FCS data (Supplementary Figure S7A). This may comprise both the true diffusion and a binding component, or may also be due to chromatin movements during the longer measurement times used in ASH1 FRAP experiments (18,30). In all cases, diffusion was slower than expected for the monomeric protein, suggesting that these proteins participate in high-molecular weight complexes (Supplementary Figure S7B).…”
Section: Resultsmentioning
confidence: 99%
“…These studies demonstrate that PRC1 complexes bind chromatin by simple chemical equilibria (15). Given this observation, it has been proposed that developmental transitions in PcG and TrxG regulation may be a matter of quantitative, rather than qualitative change (18). To understand dynamic aspects of regulation by PcG and TrxG proteins, it is crucial to gain quantitative information about their absolute molecule numbers, molar concentrations and kinetic chromatin-binding properties in living animals.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements show that the typical residence time of a modification enzyme on chromatin is within sub-seconds to a few minutes [4]. Experimental observations also suggest that a modified nucleosome may have higher binding affinity for the corresponding enzymes [3,[9][10][11].…”
mentioning
confidence: 96%